The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/jrsm.1192
|View full text |Cite
|
Sign up to set email alerts
|

Comparing multiple imputation methods for systematically missing subject‐level data

Abstract: When conducting research synthesis, the collection of studies that will be combined often do not measure the same set of variables, which creates missing data. When the studies to combine are longitudinal, missing data can occur on the observation-level (time-varying) or the subject-level (non-time-varying). Traditionally, the focus of missing data methods for longitudinal data has been on missing observation-level variables. In this paper, we focus on missing subject-level variables and compare two multiple i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Missing data is an ubiquitous issue longitudinal survey data (Kline, Andridge and Kaizar 2017), and is present to a modest degree in the current analysis (see Appendix 1 for missingness summary).…”
Section: Methodsmentioning
confidence: 99%
“…Missing data is an ubiquitous issue longitudinal survey data (Kline, Andridge and Kaizar 2017), and is present to a modest degree in the current analysis (see Appendix 1 for missingness summary).…”
Section: Methodsmentioning
confidence: 99%
“…The latter can be achieved by adopting imputation models with mixed effects, which also facilitates imputation of covariates that have not been measured in one or more studies. [138][139][140][141][142] Although the assumptions needed for multiple imputation cannot always be tested or may not always be met, several simulation studies have shown that its use is usually superior to complete-case analysis or the use of missing data indicators. 143 However, caution is still warranted when analyzing imputed data sets from IPD-MA, as in the presence of between-trial heterogeneity these are inherently prone to some degree of incompatibility with the data generation mechanism.…”
Section: Missing Datamentioning
confidence: 99%
“…We also focus on this situation. However, we note that several authors have studied imputation methods for missing 'level 1' variables [15][16][17]. In this setting, Kline, Andridge, and Kaizar showed that aggregating 'level 2' variables to construct an FCS conditional regression models for each 'level 1' variable (as proposed by [15]) results in underestimates of the association between the missing variables and the observed level 2 covariates [17].…”
Section: Introductionmentioning
confidence: 99%